How volunteer person-centered counselors feel they have been affected by not finding work. (2nd January 2017) - Karaoulani, Ioanna; Rodgers, Brian; Hunt, Nigel
ABSTRACT: Many person-centered therapists provide their services on a voluntary basis wishing to enrich and expand their experiences as individuals and counselors. However, while rewarding, volunteers may also be affected by the difficulties of long-term unemployment. In this study, nine volunteer person-centered counselors in Greece aged 22–65, holding a Diploma in person-centered counseling, were interviewed. Participants were asked about how their experiences of not finding paid work might be affecting both themselves and their client work. The results indicated that long-term unemployment substantially reduces the counselors' belief in their knowledge, skills, and counseling abilities while at the same time introducing doubts about their choice of profession, and even the very nature of the person-centered counseling process.